Development of 22 Polymorphic Microsatellite Loci for the Critically Endangered Morato’s Digger Toad, Proceratophrys moratoi - Arruda, Maurício Papa (Molecular Diversity Preservation International (MDPI), 2012)
The Morato’s digger toad (Proceratophrys moratoi) inhabits Brazilian moist savannas and is critically endangered due to its very limited geographic distribution, reduced number of isolated populations, and evidence of population decline and local extinctions. With the objective of providing tools for the genetic study of the species, 22 polymorphic microsatellite loci were isolated and screened using DNA extracted from samples of oral mucosa cells obtained from 113 individuals representing five remnant P. moratoi populations in the Brazilian state of São Paulo. These markers presented 2–18 alleles per locus, polymorphism information content (PIC) of 0.02–0.87, observed heterozygosity of 0.02–0.96 and expected heterozygosity of 0.02–0.87. Three of the loci deviated significantly from Hardy–Weinberg equilibrium in one of the populations, possibly due to the presence of null alleles. Significant linkage disequilibrium was also detected between three pairs of loci. The molecular markers developed in this study were able to discriminate each of the individuals sampled (identity analysis). This means that they will be extremely useful for future genetic studies applied to the conservation of P. moratoi, providing a baseline for estimating the levels of genetic diversity, pedigrees, inbreeding, and population structure, which will be essential for the development of effective genetic management programs.